2001
DOI: 10.1177/0146167201273003
|View full text |Cite
|
Sign up to set email alerts
|

On the Social Nature of Personality: Effects of Extraversion, Agreeableness, and Feedback about Collective Resource Use on Cooperation in a Resource Dilemma

Abstract: The present research investigated how individual differences in Extraversion and Agreeableness affect cooperation in an experimental resource dilemma. Manipulated feedback indicated either that the common resource was being used at a sustainable rate or that it was being rapidly depleted. As predicted, Extraversion was generally negatively related to cooperation, whereas Agreeableness was generally positively related to cooperation. Whereas individuals high in Extraversion and individuals low in Agreeableness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
105
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 71 publications
(154 reference statements)
7
105
0
1
Order By: Relevance
“…These include, but are not limited to: personality (e.g., Koole, Jager, Vlek, & Hofstee, 2001;Smith & Bell, 1993);…”
Section: Factors Associated With Cooperation In Commons Dilemmasmentioning
confidence: 99%
See 1 more Smart Citation
“…These include, but are not limited to: personality (e.g., Koole, Jager, Vlek, & Hofstee, 2001;Smith & Bell, 1993);…”
Section: Factors Associated With Cooperation In Commons Dilemmasmentioning
confidence: 99%
“…In regard to conditions under which individuals believe that previous harvesters have behaved in an exploitive manner, other past research suggests that when a resource is perceived to be dwindling individuals will compensate by conserving (e.g., Loomis et al, 1994;Koole, Jager, van den Berg, Vlek, & Hofstee, 2001). For example, Loomis and colleagues (1994) found that when groups of individuals harvested from a shared resource that began to reach very low levels, they reduced their harvesting to slow the depletion.…”
Section: Commons Dilemmas In the Real Worldmentioning
confidence: 99%
“…when players were informed that other players would be given the opportunity to fine them based on their contributions [28]. To further confuse matters, Koole et al [24] did not find a reliable effect of neuroticism on resource depletion in a collective resource dilemma, and Volk et al [23] did not find a robust relationship between neuroticism (emotional stability) and contributions in a one-shot PGG. Similarly, neither Zettler et al [39] nor Pothos et al [25] observed a robust effect of neuroticism or BIS on cooperation in a one-shot PD.…”
Section: Introductionmentioning
confidence: 96%
“…Indeed, individuals high in agreeableness were more likely to be conditional cooperators in a 'one-shot' PGG (i.e. only one round of the game is played) [23] and more likely to cooperate unconditionally in a commons dilemma when the resource was severely threatened [24]. They were also more likely to cooperate in a one-shot PD, but only when the payoff structure was such that cooperation, rather than defection, was the optimal strategy [25], and in the first round of an iterated PD (IPD; i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation